Long-Term Stability of Metallic Iron inside Carbon Nanotubes - Kappen, P; Rider, A; Pigram, P. J; Brack, N (Journal of physical chemistry. C, 2011)
Carbon nanotubes are important for the production of new materials with interesting electronic, magnetic, and mechanical properties. This study addresses the behavior of iron phases inside multiwalled carbon nanotubes grown from catalytic chemical vapor deposition (CCVD). Previous work had shown that the presence of metallic iron inside nanotubes is closely linked to CCVD production of long nanotubes at high yield. The long-term stability of the iron inside the nanotubes has not been investigated and is subject of this study. X-ray absorption spectroscopy (XAS) and X-ray photoelectron spectroscopy are employed to evaluate elemental and structural detail of nanotubes during storage over a period of close to three years. A basic heat treatment is also performed to assess the stability upon moderate thermal stress. The XAS results show that the metallic phases are stable over time and after heating. These outcomes demonstrate that the carbon nanotubes served as effective containers for the preservation of otherwise reactive phases; an important step toward producing products where the degradation of the contents inside carbon nanotubes is of critical importance.